Satellite tracking data of wild-release red-crowned cranes in the Yancheng National Nature Reserve for Rare Birds from 2022 to 2023 - Hu, Xinyi; Wu, Dawei; Chen, Hao; Chen, Weihua; Chen, Guoyuan; Hu, Wei; Chen, Taiyu; Lu, Changhu (PANGAEA, 2024)
In November 2022, February 2023, and May 2023, six red-crowned cranes were released into the Yancheng National Nature Reserve for Rare Birds, to increase the western migratory population of the red-crowned crane. All the released individuals were bred in captivity within the reserve and fitted with satellite transmitters (platform transmitter terminals, PTT). The satellite transmitters used were HQLG4037S, weighing less than 3% of the body weight of the red-crowned cranes. By utilizing the Global Messenger Tracking Data Service Platform, real-time monitoring of individuals was conducted (HQXS, 2019). The data, including the latitude and longitude, altitude, motion trajectory, were collected for the cranes. Invalid data were eliminated, and only data with a positioning error of < 10 m were retained.
Keywords: Flight altitude; Red-crowned crane; satellite tracking